2014
DOI: 10.1556/jep.12.2014.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Manipulated luxury-apartment ownership enhances opposite-sex attraction in females but not males

Abstract: Abstract. Manipulated prestige car ownership has been shown previously to enhance male attractiveness. In the current study the illusion of status-linked property ownership was achieved by presenting a target male and female (matched for attractiveness) adopting a casual posture standing in either a 'high status' (luxury apartment) or a 'neutral status' (standard apartment) context. A between-subjects design was used with the photographic stimuli presented amongst other masking stimuli and rated for attractive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 57 publications
1
27
3
Order By: Relevance
“…The FWHR is not the sole facial metric associated with masculine dominance and aggressiveness; studies have implicated jaw width [ 69 ], brow height, eye length, and mouth width [ 70 ]. However, the FWHR is well-situated in the upper face, where humans preferentially extract information about threat [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…The FWHR is not the sole facial metric associated with masculine dominance and aggressiveness; studies have implicated jaw width [ 69 ], brow height, eye length, and mouth width [ 70 ]. However, the FWHR is well-situated in the upper face, where humans preferentially extract information about threat [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the cheerleader effect also occurs through a process of social inference, wherein observers use the presence of other faces in the group to infer that the evaluated individual likely possesses desirable characteristics, such as being friendly or kind, which consequently increases their perceived favourability to the observer 62 . Importantly, this type of social learning is not specific to mate selection 63 , or even to the presence of human faces, since favourable characteristics, including attractiveness, are attributed to faces shown with possessions that signal wealth or social status [64][65][66][67][68][69][70] . Therefore, a social inference mechanism could also explain why a small increase in attractiveness is found for faces shown among groups of houses.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, men are particularly selective when seeking a mate for a long-term relationship (Geary et al, 2004), which implies that women should also engage in the signaling process. However, Griskevicius et al (2007) and Sundie et al (2011) found women did not spend more money on conspicuous luxuries in a mating context compared to a neutral context, and Sundie et al (2011), Dunn andSearle (2010), and Dunn and Hill (2014) found that men's judgments of a woman's attractiveness were independent from her conspicuous consumption patterns. Instead, a more plausible explanation for women's conspicuous consumption behavior is female intrasexual competition for status (Miller, 2009;Wang and Griskevicius, 2014).…”
Section: Female Luxury Consumptionmentioning
confidence: 97%